(untitled) (The Review of Diabetic Studies, 2024)
The global landscape of illicit drug consumption has undergone a radical transformation over the past decade, characterized by the unprecedented proliferation of New Psychoactive Substances (NPS) and high-potency synthetic opioids. This shift has precipitated a complex syndemic crisis that intertwines public health security, mental health management, and addiction epidemiology. As the chemical diversity of the drug supply expands—with the United Nations Office on Drugs and Crime (UNODC) reporting over 80 different synthetic opioids and a vast array of designer benzodiazepines—traditional toxicological screening methods have become dangerously insufficient. This systematic review evaluates the critical necessity of transitioning from presumptive immunoassay (IA) screening to advanced, definitive laboratory technologies, specifically Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) and High-Resolution Mass Spectrometry (HRMS), to mitigate these emerging threats. Current epidemiological data indicates that standard immunoassay panels exhibit alarming false-negative rates when challenged with modern synthetic compounds. Clinical studies reveal that up to 28% of benzodiazepine use and 50% of cocaine use may go undetected by standard screens in specific patient cohorts, and the "invisible" nature of novel synthetic opioids (NSOs) like nitazenes and fentanyl analogues creates a profound diagnostic blind spot. This diagnostic gap compromises clinical decision-making in psychiatric emergency settings, where substance-induced psychoses are frequently misdiagnosed as primary psychiatric disorders due to the inability of standard screens to detect the etiological agents. Furthermore, in the context of Opioid Agonist Therapy (OAT), the lack of precise testing undermines treatment retention and patient safety. Drawing on data from global early warning systems (EWS) such as Euro-DEN Plus and the Drug Abuse Warning Network (DAWN), alongside comparative diagnostic accuracy studies, this report demonstrates that the implementation of definitive testing significantly enhances treatment outcomes. Evidence suggests that weekly definitive screening is associated with a greater than six-fold increase in the odds of one-year treatment retention for OAT patients compared to less frequent monitoring. Moreover, the integration of clinical toxicology data with wastewater-based epidemiology (WBE) offers a robust framework for national health security, enabling the rapid triangulation of emerging chemical threats before they result in mass casualty events. Despite perceived economic barriers, cost-benefit analyses reviewed herein suggest that comprehensive LC-MS/MS screening can reduce per-sample costs by approximately 70% compared to expansive immunoassay panels while providing superior analytical specificity. Consequently, this report argues for a paradigmatic shift in clinical and forensic toxicology: moving Definitive Screening from a confirmatory luxury to a primary standard of care. Such a shift is essential to strengthen global health security, optimize mental health interventions, and improve individual patient outcomes in the face of an increasingly volatile and synthetic drug market.